Screening of Wheat Genotypes under Drought and Salinity Stresses During Germination and Seedling Traits - Husain, Muhammaed Jawad; AL-Jobori, Kamil M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
This study examines wheat genotypes under combined and single drought and salinity stresses, assessing germination and seedling growth traits, as environmental issues like high salinity and drought significantly impact plant life.. The experiment was carried out to meet these goals. To identify the most and least tolerant genotypes, 16 genotypes were tested. Water potentials of 0. -0.5, -1.0, -1.5, and -2.0Mpa were used as treatments to create water stress by adding polyethylene glycol (PEG-6000) and sodium chloride together(D+S). After 15 days of putting seeds in Petri dishes, growth parameters were assessed, including germination percentage (%), speed of emergence (%), seedling vigour index, shoot length (cm), and fresh and dried weight of shoot, root, and whole seedling (g). Results showed that all genotypes demonstrated a decrease in germination and biomass with an increase in stress-induced water stress, where germination (%) and biomass are inversely correlated with combined stress. While the genotypes Babil, Hashimia, Baraka, Buhooth 158, Tamooz 3, and Uruk did not germinate at -2.0 MPa, Latyfia showed better germination (76.66%), higher speed of emergence (81.93%), seedling vigor index (5.70), seedling length (7.50 cm), root and seedling fresh weight (0.0450 and 0.0650 g) and root and seedling dry weight (0.0312 and 0.0411 g). Iba99 exhibited the lowest values in the majority of traits at -2.0 MPa. In conclusion, each genotype behaved differently in response to salinity, drought, or levels of combined stresses during germination. The genotype Latifya performed better in the study compared to the other genotypes because it was better able to endure the effects of these stresses. Consequently, it can be utilized as breeding stock to increase the wheat crop’s tolerance to salinity and drought. The study’s findings increase knowledge of how plants react to challenges like salt, drought, and both in combinationز